Round and round: Examining teaching residents' participation in and reflections on education rounds. (2015) - Reagan, Emilie Mitescu; Chen, Crystal; Roegman, Rachel; Zuckerman, Kelly Gavin
Highlights: We examine preservice teachers' participation in education rounds. Rounds provided opportunities for investigation of teaching practice with a community. There were multiple purposes for education rounds. If used, education rounds must be integrated purposefully into teacher preparation. Abstract: In teacher preparation, the education rounds model has the potential to facilitate opportunities for preservice teachers to engage as part of a professional community and inquire into their teaching practice. This qualitative study examines the education rounds model in a graduate-level teacher residency program in New York City. We analyze how a cohort of 20 preservice teachers framed their teaching practice and reflected on opportunities for learning through education rounds. Findings suggest that the education rounds process highlighted gaps in preservice teachers' understandings of how, when, and why to use particular instructional strategies and principles. However, in most cases, education rounds supported the development of tools to study teaching in and with a community of learners.